The Effect of Food Commodity Price Fluctuations on Inflation in East Java - Intan Lestari (Journal of Current Studies in SDGs, 2025)
Objective: This study aims to analyze the effect of price fluctuations of food commodities shallots, rice, and cayenne pepper—on inflation in East Java. Inflation is a persistent economic issue that affects all regions in Indonesia, often triggered by shock factors such as volatile commodity prices. Understanding the dynamics between key food prices and inflation is crucial for formulating effective regional economic policies. Method: This quantitative research uses monthly time-series data from 2021 to 2023 and applies the Vector Error Correction Model (VECM) for analysis. The data were obtained from the East Java Staple Food Availability and Price Development Information System and the Central Statistics Agency. The research includes stationarity tests, cointegration tests, and impulse response analysis, all conducted using EViews 12 software. Results: In the short term, shallot prices have a negative and significant effect on inflation, rice prices have a positive and significant effect, and cayenne pepper prices show a positive but insignificant effect. In the long term, both shallot and rice prices exert a positive and significant impact, while cayenne pepper prices have a negative and significant effect on inflation in East Java. Novelty: Unlike previous studies, this research simultaneously analyzes the short- and long-term effects of multiple staple food commodities on regional inflation using recent post-pandemic data. The study contributes to a better understanding of how different food price shocks affect inflation dynamics at the provincial level, supporting the design of more targeted inflation control strategies in East Java.